2017
DOI: 10.1111/jwas.12477
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Commercial‐scale Approaches for Cryopreservation of White Crappie, Pomoxis annularis, Sperm

Abstract: Crappie, Pomoxis spp., are popular game fish throughout North America and are produced by public and private hatcheries. However, production is limited by a lack of information on tank culture and induced spawning methods. Development of techniques for storage of sperm and in vitro fertilization would increase flexibility in spawning. Therefore, techniques for sperm cryopreservation were examined in white crappie, Pomoxis annularis. Sperm from adult wild white crappie were used to evaluate sperm extender, cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 17 publications
1
15
2
Order By: Relevance
“…In comparison, the present study found black‐stripe black crappie sperm with 5% DMSO was more effective at fertilizing white crappie eggs (38%) than sperm cryopreserved in 10% methanol (22%). Although not directly comparable due to higher sperm:egg ratios used by Culpepper et al (2018) (3.19 × 10 5 vs. 1.59 × 10 5 in the present study), this study had higher fertilization rates in white crappie eggs than those of Culpepper et al's study. Interestingly, black‐stripe black crappie sperm was more effective at fertilizing white crappie eggs than white crappie sperm.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…In comparison, the present study found black‐stripe black crappie sperm with 5% DMSO was more effective at fertilizing white crappie eggs (38%) than sperm cryopreserved in 10% methanol (22%). Although not directly comparable due to higher sperm:egg ratios used by Culpepper et al (2018) (3.19 × 10 5 vs. 1.59 × 10 5 in the present study), this study had higher fertilization rates in white crappie eggs than those of Culpepper et al's study. Interestingly, black‐stripe black crappie sperm was more effective at fertilizing white crappie eggs than white crappie sperm.…”
Section: Discussioncontrasting
confidence: 81%
“…Motility was estimated within 10 s of sperm activation using computer-assisted sperm analysis (CASA) (HTM-CEROS, version 14 Build 013, Hamilton Thorne Biosciences, Beverly, MA). System settings for assessing progressive motility were minimum contrast, 60; minimum cell size, 2 μm; number of frames for recording, 100; average-path velocity cut-off, 25 μ/s; straight-line velocity cut-off, 1 μ/s ( Culpepper et al, 2018 ). Three measurements, each from a different field of view, were collected for each sample and the average initial motility calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of protocols for these species led to interest in the development of protocols for crappie, although most crappie production has been done extensively in ponds (Morris & Clayton, 2009) with variable techniques and success (Culpepper & Allen, 2016b). However, the development (Al‐ablani & Phelps, 1997; Arslan & Phelps, 2004; Gomelsky et al, 2002) and recent refinement (Cuevas‐Uribe et al, 2009; Culpepper & Allen, 2016b) of techniques for hormone induced spawning, tank holding procedures, out‐of‐season spawning techniques (Culpepper & Allen, 2016a) and sperm cryopreservation (Culpepper et al, 2018; Shirley et al, accepted) have allowed for more intensive crappie spawning techniques to be studied.…”
Section: Discussionmentioning
confidence: 99%